Ca2+-induced permeabilization of the Escherichia coli outer membrane: comparison of transformation and reconstitution of binding-protein-dependent transport. - Bukau, B (1985)
Ca2+ treatment renders the outer membrane of Escherichia coli reversibly permeable for macromolecules. We investigated whether Ca2+-induced uptake of exogenous protein into the periplasm occurs by mechanisms similar to Ca2+-induced uptake of DNA into the cytoplasm during transformation. Protein import through the outer membrane was monitored by measuring reconstitution of maltose transport after the addition of shock fluid containing maltose-binding protein. DNA import through the outer and inner membrane was measured by determining the efficiency of transformation with plasmid DNA. Both processes were stimulated by increasing Ca2+ concentrations up to 400 mM. Plasmolysis was essential for a high efficiency; reconstitution and transformation could be stimulated 5- and 40-fold, respectively, by a high concentration of sucrose (400 mM) in cells incubated with a suboptimal Ca2+ concentration (50 mM). The same divalent cations that promote import of DNA (Ca2+, Ba2+, Sr2+, Mg2+, and Ni2+) also induced import of protein. Ca2+ alone was found to be inefficient in promoting reconstitution; successive treatment with phosphate and Ca2+ ions was essential. Transformation also was observed in the absence of phosphate, but could be stimulated by pretreatment with phosphate. The optimal phosphate concentrations were 100 mM and 1 to 10 mM for reconstitution and transformation, respectively. Heat shock, in which the cells are rapidly transferred from 0 to 42 degrees C, affected the two processes differently. Incubation of cells at 0 degrees C in Ca2+ alone allows rapid entry of protein, but not of DNA. Transformation was observed only when exogenous DNA was still present during the heat shock. Shock fluid containing maltose-binding protein inhibited transformation (with 6 microgram of DNA per ml, half-maximal inhibition occurred at around 300 microgram of shock fluid per ml). DNA inhibited reconstitution (with 5 microgram of shock fluid per ml, half-maximal inhibition occurred at around 3 mg of DNA per ml).